FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA PERUSAHAAN SUB-SEKTOR MAKANAN DAN MINUMAN - Nia Agustina Dewi; Siti Nurlaela; Endang Masitoh (Universitas Prof.Hazairin,SH Bengkulu, 2020)
This research was conducted in the food and beverage sub-sector companies listed on the Stock Exchange in the 2013-2018 period. In this study aims to determine the effect of leverage, liquidity, activity ratios and company size on profitability in the food and beverage sub-sector listed on the Stock Exchange in 2013-2018. The type of data used in this study is secondary data. The samples used in this study were 8 companies. Sampling in this study was conducted by purposive sampling method. The method of data analysis uses multiple linear regression test. The results of this study, namely: First, leverage does not affect profitability. Second, liquidity has no effect on profitability. Third, the activity ratio has no effect on profitability. Fourth, company size affects profitability. This research is beneficial for academics to be able to improve, improve their ability and understanding and can solve problems raised by the author regarding Leverage, Liquidity, Activity Ratios and Firm Size to Profitability.